Trends in respiratory syncytial virus bronchiolitis hospitalizations in children less than 1 year: 2004–2012. (2nd April 2016) - Sanchez-Luna, Manuel; Elola, Francisco J.; Fernandez-Perez, Cristina; Bernal, Jose L.; Lopez-Pineda, Adriana
Abstract: Objective To analyze trends in health outcomes and the influence of risk factors in children under 1 year with acute bronchiolitis due to respiratory syncytial virus (RSV bronchiolitis). A risk-adjustment model for RSV bronchiolitis in-hospital mortality was also developed. Research design and methods Retrospective study of hospitalizations for RSV bronchiolitis in children aged <1 year from 2004 to 2012. We used nationally representative data from the Spanish National Health Service records. Results Over the study period, the annual hospital discharges for RSV bronchiolitis ranged between 6390 and 8637. The annual in-hospital mortality rate ranged from 120 (2004) to 69 (2012) per 100, 000 hospitalizations and the mean length of stay decreased steadily from 6.5 to 5.2 days ( p < 0.001); 98.3% of hospitalizations for RSV bronchiolitis were children without risk factors. The in-hospital mortality rate due to RSV bronchiolitis in children with risk factors was 18.8 times higher than non-high-risk children and, in adjusted analyses, the OR of in-hospital mortality due to RSV bronchiolitis was higher than that due to other causes. Limitations This study is a retrospective analysis, based on administrative data. It does not include data about pre- or in-hospital treatments, and has the limitations inherent in procedures for determining risk-adjusted mortality rates. Socioeconomic and environmental factors have not been considered in this study. Conclusions RSV bronchiolitis is a leading cause of hospitalizations for infants under 1 year and has not shown incidence reduction over a 9 year period. Risk factors increase the in-hospital mortality risk and it is higher if the hospitalization cause is RSV bronchiolitis than any other reason.